Computerization of the Discipline of Jurisprudence: Presentation and Evaluation - Hesham Mohammed Alsaeed (Journal of Islamic Studies, 2016)
This research is concerned with the virtues of computerizing the discipline of Islamic fiqh (jurisprudence). Computer technology has rendered immensely great services to sciences, including the foundations of fiqh and related rules, differences and documentation. In the field of fiqh, related databases have been developed, and so have related texts, media, sites and applications. Computer advances are facilitating access to fiqh sciences and issues. They have provided current researchers with new techniques, securing greater accuracy, inductive competency, and hence opening new horizons for fiqh researchers, and overcoming many frequently encountered obstacles. The present research attempts to explain the computerization of the discipline of fiqh foundations, to show its forms and its contribution to the discipline, and to demonstrate and evaluate the most important related applications. The research makes a number of recommendations deemed good for more competent computerization of the discipline of fiqh foundations.